Geotechnical Performance Evaluation of Flood-Impacted Subgrade of Fori Road, Maiduguri, Borno State, Nigeria - Kobiowu, A.; Ibrahim, Y.; Bukar, A. G.; Halliru, I. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2026)
This research investigates the properties and suitability of subgrade soils in Fori area of Maiduguri for road pavement foundations in flood prone environments. Soil samples were collected from three locations along Fori road over an approximately 300 m stretch, after the Fori community bridge area, Maiduguri. Some of the soil sample properties analysed includes grain size distribution, Atterberg limits, Standard Proctor compaction and California Bearing Ratio (CBR) tests on soil samples from 0.5 m and 1.0 m depths. The results of the Particle size distribution and Atterberg limits show that the soils is classified as fine sand A-3(0) according to the America Association for State Highway and Transportation Officials (AASHTO), exhibiting low cohesion and high moisture sensitivity. However, compaction results indicated a relatively flat moisture density curves, with maximum dry densities of 1.71 g/cm³ (0.5 m) and 1.55 g/cm³ (1.0 m) corresponding to optimum moisture contents of 12.89 % and 19.4 %, respectively. Soil compressibility was quantified using the liquid limit, yielding values of 0.11 and 0.10, which indicates moderate compressibility of the flood impacted subgrade. Similarly soaked CBR values showed a significant strength reductions down to 1.36 % (0.5 m) and 2.85 % (1.0 m) after 48 hours. The soil is thus, regarded as “very poor” category for subgrades according to TRRL standards. Comparative analyses with existing literature shows that these characteristics are typical of fine grained, non-cohesive soils under flooding and are consistent with global observations of weakened subgrades. The study therefore concludes that the native soils are unsuitable for direct use as pavement subgrades in their natural state. To ensure durable road performance in Fori’s flood prone environment, measures such as chemical stabilization, profile elevation, improved drainage and possible geosynthetic reinforcement are recommended.